2013
DOI: 10.3325/cmj.2013.54.257
|View full text |Cite
|
Sign up to set email alerts
|

The risk of false inclusion of a relative in parentage testing – an in silico population study

Abstract: AimTo investigate the potential of false inclusion of a close genetic relative in paternity testing by using computer generated families.Methods10 000 computer-simulated families over three generations were generated based on genotypes using 15 short tandem repeat loci. These data were used in assessing the probability of inclusion or exclusion of paternity when the father is actually a sibling, grandparent, uncle, half sibling, cousin, or a random male. Further, we considered a duo case where the mother’s DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The difficulty of rejecting close relatives as parents is a known problem in exclusion analysis (Lee et al . ). An additional challenge within our sample was that several horses were related in multiple branches of the family (for example, a half sibling pair sharing a sire but with dams that were also full siblings).…”
Section: Resultsmentioning
confidence: 97%
“…The difficulty of rejecting close relatives as parents is a known problem in exclusion analysis (Lee et al . ). An additional challenge within our sample was that several horses were related in multiple branches of the family (for example, a half sibling pair sharing a sire but with dams that were also full siblings).…”
Section: Resultsmentioning
confidence: 97%
“…With the GlobalFiler TM system, Ochiai predicted that the probability of matches with only 1 mismatch in 21 STRs for full siblings was 23.5% ( Ochiai et al, 2016 ). Lee simulated families with 15 STRs in silico; the false inclusion rate was 19.0% when considering a sibling as the parent ( Lee et al, 2013 ). These data suggested that the current STR systems are insufficient to distinguish a close relative from the true parent in deficiency cases, and supplementary investigations need to be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of strict guidelines to conduct motherless cases were sufficient to avoid false inclusions between unrelated children and alleged fathers in our data set of more than 20 000 cases. The single inclusion found highlights that relatedness is a concern in motherless cases 1,7,10 and calls attention to the importance of obtaining information on family circumstances before the analysis and especially to the importance of testing the mother in all situations, even if maternity is not disputed.…”
Section: Discussionmentioning
confidence: 99%
“…The motherʼs absence increases the probability of false paternity inclusion, 1 and several studies have reported that in some circumstances motherless analysis can result in incorrect paternity calls and have advised precaution in such cases. [2][3][4][5][6][7][8][9][10][11][12] Despite the challenges, motherless testing continues to be used, for example, (a) when the mother is unavailable or (b) in some countries, motherʼs participation is not mandatory for tests that are for personal (nonlegal) purposes.…”
Section: Introductionmentioning
confidence: 99%